Surgical Treatment for Massive Pulmonary Embolism and a Thrombus Crossing a Patent Foramen Ovale: Impending Paradoxical Embolism - Ito, Fusahiko; Watanabe, Masazumi; Katsumata, Chieko (Japanese Journal of Vascular Surgery, 2014)
A 47-year-old man was admitted to our institution complaining severe dyspnea. The ultrasound cardiograph showed marked dilatation of right ventricle, pulmonary hypertension estimated 56 mmHg and the floating thrombi of bilateral atrium. The enhanced CT revealed thrombosis of bilateral pulmonary artery. An emergency operation was performed. The right atrium was opened under cardiac arrest and a tubular thrombus trapped in the patent foramen ovale was removed. Also massive fresh thrombi were removed from the bilateral main pulmonary artery. The patient discharged without symptoms. Early surgical treatment is necessary for avoiding paradoxical embolisms.